Dynamics of perioperative pancreatic exocrine function in patients undergoing reconstruction after gastrectomy for gastric cancer - Takashi, Nakayama; Katsutoshi, Shoda; Kensuke, Shiraishi; Shinji, Furuya; Naohiro, Hosomura; Hidenori, Akaike; Yoshihiko, Kawaguchi; Hidetake, Amemiya; Hiromichi, Kawaida; Daisuke, Ichikawa (Surgery Today, 2024)
Background Each method of reconstruction after gastrectomy results in a change in the digestive and absorptive status. However, there are few reports on the changes in pancreatic exocrine function after gastrectomy. We conducted this study to investigate the dynamics of pancreatic exocrine function after gastrectomy according to the method of reconstruction performed. Methods The subjects of this study were 45 patients who underwent pancreatic exocrine function tests preoperatively and postoperatively, from among all patients who underwent gastrectomy for gastric cancer at our hospital between September, 2020 and March, 2022. We assessed pancreatic exocrine function using the Pancreatic Function Diagnostant (PFD) test. Result The mean preoperative PFD test result values for the distal gastrectomy (DG) Billroth I reconstruction (B–I) group and the DG Roux-en-Y reconstruction (R–Y) group were 62.6 and 67.3 ( p = 0.36), respectively, and the mean postoperative PFD test result values for each group were 65.8 and 46.9 ( p = 0.0094), respectively. A significant decrease in postoperative pancreatic function was observed in the DG R-Y group but not in the DG B–I group. The logistic regression analysis identified that age and the R–Y group were significantly correlated with a 10% decrease in the PFD value after gastrectomy. Conclusions Our study suggests that R–Y reconstruction may result in more impaired pancreatic exocrine function than B–I reconstruction.